Karakterisasi Simplisia dan Skrining Fitokimia Ekstrak Etanol Kayu Secang (Caesalpinia Sappan L) - Dhea Nur Fadhilah; Suharyanisa; Dumartina Hutauruk; Siti Nurbaya (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Secang wood is one of the plants that contains many antioxidants, secondary metabolites and antibacterial compounds. This study aims to determine characterization of simplicia and chemical substances of Secang wood extract. Secang wood which was already in the form of simplicia was extracted by maceration using 96% ethanol solvent and the extract was concentrated with a rotary evaporator at a temperature of 40°C, then screening and characterization tests were carried out. The results of this study showed that phytochemical screening of the ethanol extract of sappan wood (Caesaloinia sappan L) showed the presence of flavonoid, tannin, saponin, alkaloid, steroid, and phenolic compounds. Characterization of simplicia obtained results at water content (3.95%) water soluble extract (11.01%), ethanol soluble extract (17.22%), total ash content (1.81%) and non-soluble ash content. acid soluble (0.28%).